2018
DOI: 10.1051/epjconf/201816702003
|View full text |Cite
|
Sign up to set email alerts
|

Ion energy distributions from laser-generated plasmas at two different intensities

Abstract: Abstract. Laser-generated non-equilibrium plasmas were analyzed at Brookhaven National Laboratory (NY, USA) and MIFT Messina University (Italy). Two laser intensities of 10 12 W/cm 2 and 10 9 W/cm 2 , have been employed to irradiate Al and Al with Au coating targets in high vacuum conditions. Ion energy distributions were obtained using electrostatic analyzers coupled with ion collectors. Time of flight measurements were performed by changing the laser irradiation conditions. The study was carried out to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This means that if the target is thicker than 50 nm, the damage to the substrate can be suppressed, and a laser target with a long lifetime can be realized. Although a higher laser energy density is required to increase the ion current, it has been previously demonstrated that a target with a thickness of the order of 100 nm is useful to avoid the ablation of the substrate for a laser power density of 10 9 W/cm 2 or more through an experiment using the target of Al coated by thin Au [18]. The above results show that the Xe 1+ ion beam current required for HIF can be obtained by irradiating the laser with a power density of 3 × 10 8 W/cm 2 every 72 s, which corresponds to a frequency of 0.014 Hz when the xenon pressure is maintained at 8 × 10 −4 Pa.…”
Section: Resultsmentioning
confidence: 99%
“…This means that if the target is thicker than 50 nm, the damage to the substrate can be suppressed, and a laser target with a long lifetime can be realized. Although a higher laser energy density is required to increase the ion current, it has been previously demonstrated that a target with a thickness of the order of 100 nm is useful to avoid the ablation of the substrate for a laser power density of 10 9 W/cm 2 or more through an experiment using the target of Al coated by thin Au [18]. The above results show that the Xe 1+ ion beam current required for HIF can be obtained by irradiating the laser with a power density of 3 × 10 8 W/cm 2 every 72 s, which corresponds to a frequency of 0.014 Hz when the xenon pressure is maintained at 8 × 10 −4 Pa.…”
Section: Resultsmentioning
confidence: 99%